دور التكنولوجيا المالية في تعزيز الشمول المالي في الجزائر - بوجمعة، ياسين; غربي، خليل; وروينة، مصعب (University Of Eloued جامعة الوادي, 2024)
تهدف الورقة البحثية إلى إبراز دور التكنولوجيا المالية في تعزيز الشمول المالي، وذلك من خلال توسيع بقعة المعاملات المالية وتمكين كل أفراد المجتمع الواحد من الوصول والإستفادة من الخدمات المالية بغرض تلبية إحتياجاتهم بأقل وقت وتكلفة. وقد ساهمت تطبيقات وأدوات التكنولوجيا المالية من تحسين وتطوير أداء المصارف لسهولة الوصول إليها وإنخفاض تكلفتها، وفي الوقت ذاته تعتبر تحديا كبيرا لما تحوط به من مخاطر ، وعليه يجب على المصارف إستغلال هذه الأدوات المالية بطريقة مثلى من أجل حماية عملائها وتحسين أدائها وإستمراريتها. Abstract: The research paper aims to shed the light on the role of financial technology in enhancing financial inclusion by expanding the scope of financial transactions and enabling all members of society to access and benefit from financial services in order to meet their needs in less time and at lower cost. Financial technology applications and tools have contributed to improve and develop the performance of banks because their access to them is easy and they are costless . At the same time, they pose a significant challenge due to the risks associated with them. Therefore, banks must utilize these financial tools in an optimal manner to protect their customers and improve their performance and sustainability.
The role of financial technology in enhancing financial inclusion in Algeria
مداخلة
Keywords: التكنولوجيا المالية; الشمول المالي; القطاع المصرفي; الخدمات المصرفية; التحول الرقمي; Financial technology; financial inclusion; banking sector; banking services; digital transformation